PERANAN MODAL SOSIAL DALAM MEMPERTAHANKAN KEAKRABAN ASOSIATIF ANTARA PENGURUS YAYASAN GURU DAN MASYARAKAT PADA YAYASAN KARUNA DIPA PALU - Adawiyah Pettalongi (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2022)
The purpose of this research is to analyze and explain efforts to maintain the associative intimacy of foundation administrators, teachers and the community at the Karuna Dipa Palu Foundation. The research method used is descriptive qualitative, with a phenomenological approach. This research is intended to describe systematically, objectively and actual to the object under study. This research focuses on social trust and strengthening common interests in maintaining the associative closeness of foundation administrators, teachers and the community. Sources of data were obtained from informants, foundation administrators, teachers, students, parents of students and the community through observation techniques, interviews, documentation. The research results show that; (a) The associative familiarity that occurs among the board of foundations, teachers and the community at the Karuna Dipa foundation is caused by trust, social (b) Strengthening shared interests between foundation administrators, teachers and the community, encourages the creation of harmonious cooperation, good social relations dynamic or associative social interaction